Microbiological profile of central line-associated bloodstream infections at a tertiary care facility - Ralte, Lalrinawmi; Iravane, Jyoti A.; Harbade, Mangala S.; Onkari , Amruta (International Journal of Research in Medical Sciences, 2025)
Background: High-risk and critically ill patients admitted to the ICU often require catheter insertion for administering fluids, blood products, medications, and performing hemodynamic monitoring. Healthcare-associated infections (HAIs) are common in the ICU due to prolonged hospital stays. Central line-associated bloodstream infections (CLABSI) are significant healthcare-associated infections that necessitate surveillance to decrease their occurrence. This study aims to identify the etiological agents and AST patterns of CLABSI in the Medicine ICU. Methods: A hospital-based surveillance study was conducted from January to December 2023 in the medicine ICU. Blood samples were collected from suspected patients, processed, organisms isolated, and their antibiotic susceptibility tested following our department’s SOPs. CLABSI was diagnosed as per the AIIMS guidelines. CLABSI rates were calculated monthly as part of an HIC surveillance. IPC measures were implemented to reduce the CLABSI rate under surveillance. Results: Out of 628 blood samples received from the medicine ICU, 178 (28.3%) were positive by culture, and 450 were sterile. Of the 178 positive samples, 65 (10.35%) cases were HAI BSI, with 19 (3.02%) being CLABSI HAI and 46 (7.32%) non-CLABSI HAI. Among CLABSI HAI, Gram-negative bacteria (GNBs) are the most common organisms, accounting for 68.4% of isolates, while Gram-positive bacteria (GPBs) contribute 31.6%. Conclusions: Excessive use of invasive procedures increases the risk of MICU patients becoming colonized with highly resistant bacteria. Identifying the range of bacteria causing BSI helps clinicians apply proper management strategies and antibiotic policies to improve patient outcomes.